Day 2 Tue, November 16, 2021 2021
DOI: 10.2118/207498-ms
|View full text |Cite
|
Sign up to set email alerts
|

Expanding Polymer Injectivity Tests on a Second Giant Carbonate UAE Oil Reservoir at High Salinity & High Temperature Conditions.

Abstract: Over the last few years, ADNOC has systematically investigated a new polymer-based EOR scheme to improve sweep efficiency in high temperature and high salinity (HTHS) carbonate reservoirs in Abu Dhabi (Masalmeh et al., 2014). Consequently, ADNOC has developed a thorough de-risking program for the new EOR concept in these carbonate reservoirs. The de-risking program includes extensive laboratory experimental studies and field injectivity tests to ensure that the selected polymer can be propagated in the target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Formation of both intra-MMC and inter-MMC stabilized by cooperative ionic bonds is mostly specific for block polyampholytes [69][70][71][72]. It was found that the phase diagram of BPA-cationic polyelectrolyte system is dependent on the inter-MMC concentration and pH and may result in the formation of solution, gel or precipitate (Fig.…”
Section: Figure 3 Schematic Representation Of Formation Of Inter-mmc ...mentioning
confidence: 99%
“…Formation of both intra-MMC and inter-MMC stabilized by cooperative ionic bonds is mostly specific for block polyampholytes [69][70][71][72]. It was found that the phase diagram of BPA-cationic polyelectrolyte system is dependent on the inter-MMC concentration and pH and may result in the formation of solution, gel or precipitate (Fig.…”
Section: Figure 3 Schematic Representation Of Formation Of Inter-mmc ...mentioning
confidence: 99%
“…In recent decade, several novel synthetic polymers, such as modified HPAM-based polymers have been extensively studied for cEOR field pilot projects globally and in varying reservoir conditions [ 44 , 78 , 104 , 169 , 176 , 202 , 203 , 204 , 205 , 206 , 207 , 207 ]. Nevertheless, to the best of our knowledge, there have only been a few polymer flooding projects undertaken in carbonate reservoirs [ 175 , 208 , 209 ].…”
Section: Numerical Studies and Field Applicationsmentioning
confidence: 99%
“…Consequently, the polymer properties revealed through the PIT is to be used in enhancing field and sector models that will enable the assessment of polymer-based cEOR in myriad other giant, heterogeneous carbonate reservoirs. This is expected to contribute toward higher recovery in ADNOC and Middle Eastern carbonate oil fields [ 207 ]. Another significant study was conducted by Jabbar et al [ 204 ] on a viable sulfonated polymer (ATBS > 35 mol%) for possible employment in a super-giant carbonate field in the Middle East.…”
Section: Numerical Studies and Field Applicationsmentioning
confidence: 99%
See 2 more Smart Citations